Effects of moderate sedation induced by propofol or midazolam on intracranial pressure - Bianca Drewnowski; José Carlos Rebuglio Vellosa; Rafael Nastas Acras; Fábio André dos Santos (ABCS Health Sciences, 2024)
Introduction: Propofol and midazolam are the main options for moderate sedation in clinical practice. In addition, these drugs are used to reduce intracranial pressure in cases of intracranial hypertension, and their use in these situations is guided by limited evidence. Objective: To compare the effects of propofol and midazolam on intracranial pressure wave morphology in moderate sedation in patients undergoing upper digestive endoscopy. Methods: Sixty patients were included in this study, being divided into two groups, propofol and midazolam group. Intracranial pressure was monitored during and after upper digestive endoscopy, using non-invasive monitoring equipment developed by the company Brain4care. Arterial pressure was measured before and after the exam. Results: The propofol group had lower intracranial pressure (p=0.037) during moderate sedation compared to intracranial pressure after endoscopy and a significant decrease in systolic (p=0.0001) and diastolic pressure (p=0.001) after sedation. Midazolam, on the other hand, reduced systolic pressure (p=0.001), but didn’t change the other parameters after the procedure. There wasn’t a significant difference between the propofol and midazolam groups. Conclusion: There was no significant difference between the groups studied, however, analyses within the propofol and midazolam groups indicate that propofol, but not midazolam, causes changes in intracranial pressure in moderate sedation.